2012
DOI: 10.1111/j.1460-6984.2011.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social cognitive demand on Theory of Mind in conversations of adults with traumatic brain injury

Abstract: Background A requisite skill for successful conversation is the ability to adjust one’s language according to contextual factors. Aims This study examined one aspect of language use in context – the use of mental state terms, i.e. words that communicate thoughts, beliefs, or feelings– in conversations between adult males with and without traumatic brain injury (TBI) and familiar partners. Methods and Procedures Participants were 5 males in the chronic stage of recovery following severe TBI and 5 male peers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 59 publications
(102 reference statements)
2
55
1
Order By: Relevance
“…This type of time-saving treatment is economical and can be used for the intact component of ToM in persons with TBI for the rehabilitation purposes; 2, paying more attention to reaction time in ToM tasks; 3, conversation as a social activity in which ToM skill might play an important role. Since conversation is one type of non-laboratory tasks and requires inferences about beliefs, intentions, and emotions of addressee, it is an ideal task to evaluate ToM in the clinical populations such as TBI (49). Therefore, it is suggested that many studies be conducted by conversational tasks to assess ToM in individuals with TBI besides laboratory tasks of ToM; 4, further studies could be conducted on evaluating functional dif-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of time-saving treatment is economical and can be used for the intact component of ToM in persons with TBI for the rehabilitation purposes; 2, paying more attention to reaction time in ToM tasks; 3, conversation as a social activity in which ToM skill might play an important role. Since conversation is one type of non-laboratory tasks and requires inferences about beliefs, intentions, and emotions of addressee, it is an ideal task to evaluate ToM in the clinical populations such as TBI (49). Therefore, it is suggested that many studies be conducted by conversational tasks to assess ToM in individuals with TBI besides laboratory tasks of ToM; 4, further studies could be conducted on evaluating functional dif-…”
Section: Discussionmentioning
confidence: 99%
“…3 thermore, in the task of reading the minds in the eyes, the task was in front of the participants; there was no memorization. Nature of some tasks did not require memory loads and control questions such as conversation-based task (49). In general, to examine ToM skill, particularly in TBI, the tasks are recommended without memory load.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cognitive efficiency or cognitive health, just like physical health, is often taken for granted until it is compromised. It can be argued that optimal cognitive functioning is needed to help promote biological health (i.e., remembering to take medication [17]), mental health (i.e., being able to exert enough cognitive energy to consciously switch attention from dwelling on negative thoughts to positive thoughts [18]), social competence (i.e., attending to details in conversation [19]), personal control (i.e., decision making such as in finances [20, 21]), and life satisfaction (i.e., remembering and reflecting on personal events and deriving meaning [2224]). Based on this argument, optimal cognitive functioning is one of the most important competencies needed to help adults with HIV age successfully.…”
Section: Introductionmentioning
confidence: 99%
“…This author states that current questions about language development "continue to focus on how babies and young children "break the code" that is, how they manage to make sense of the linguistic sound that surrounds them, and then become competent users of a language". However, today another very fertile area of study is related to the changes that occur in the language and communication of adults [2][3][4].…”
Section: Introductionmentioning
confidence: 99%